2020
DOI: 10.5334/joc.99
|View full text |Cite
|
Sign up to set email alerts
|

Genesis or Evolution of Gender Differences? Worldview-Based Dilemmas in The Processing of Scientific Information

Abstract: Some issues that have been settled by the scientific community, such as evolution, the effectiveness of vaccinations, and the role of CO 2 emissions in climate change, continue to be rejected by segments of the public. This rejection is typically driven by people's worldviews, and to date most research has found that conservatives are uniformly more likely to reject scientific findings than liberals across a number of domains. We report a large (N > 1,000) preregistered study that addresses two questions: Firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 74 publications
(102 reference statements)
4
35
0
Order By: Relevance
“…We also tested the speculations put forth in previous studies [27,28,32] that negative attitudes to vaccines and positive attitudes to CAM may be driven by a shared underlying reluctance to agree with the medical consensus. Our analyses indeed revealed weak associations between vaccine attitudes and CAM use (r = -.22 --.24), which were roughly in line with previous research [31,32], and between vaccination behavior and CAM use (r = .12 -.19), but there was no clear support for the hypothesis that the associations would be explained by trait reactance and trust in doctors. These findings suggest that high trait reactance and low trust in doctors has different consequences for different people.…”
Section: Plos Onesupporting
confidence: 83%
See 1 more Smart Citation
“…We also tested the speculations put forth in previous studies [27,28,32] that negative attitudes to vaccines and positive attitudes to CAM may be driven by a shared underlying reluctance to agree with the medical consensus. Our analyses indeed revealed weak associations between vaccine attitudes and CAM use (r = -.22 --.24), which were roughly in line with previous research [31,32], and between vaccination behavior and CAM use (r = .12 -.19), but there was no clear support for the hypothesis that the associations would be explained by trait reactance and trust in doctors. These findings suggest that high trait reactance and low trust in doctors has different consequences for different people.…”
Section: Plos Onesupporting
confidence: 83%
“…Based on this, the authors speculated that people do not become vaccine hesitant because they trust CAM, but rather because they distrust conventional medicine. The connection between positive attitudes to CAM and negative attitudes to vaccines has recently been found also among parents in 18 European countries [ 30 ], and adults living in America [ 31 ]. Finally, the results from an Australian study with 2758 adults [ 32 ], indicated that the negative association between CAM and vaccine attitudes could largely be explained by magical beliefs about health, which lends support to the idea that negative attitudes to vaccinations, as well as CAM, may be due to an underlying view on health that is not evidence-based.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20] Recent work has demonstrated that Trump supporters are more likely to exhibit anti-vaccination attitudes both because of their conservativism and their higher tendency to conspiracist beliefs, with the latter a stronger predictor, and with the current US President's anti-vaccination Tweets appearing to have a causal effect on antivaccination attitudes. 21 Research using a representative sample of the US population confirms that free-market endorsement predicts vaccine rejection, 22 while populist party vote share has been found to correlate at the national level with vaccine hesitancy across Western Europe. 23 Murphy et al identified that supporting Sinn Féin or independent candidates (namely, anti-establishment candidates) rather than no party was associated with vaccine hesitancy and resistance in an Irish sample; authoritarianism and social dominance traits were also found to vary significantly with vaccine hesitancy and resistance.…”
Section: Introductionmentioning
confidence: 96%
“…In sum, our results are in line with the notion that potentially-irrational rejection of evidence is equally likely on both ends of the political-worldview spectrum, and that part of the reason that evidence rejection has been predominantly demonstrated in conservatives is that researchers have predominantly looked at rejection of evidence that is consistent with conservative worldviews. However, this presents future research with a conundrum, because a number of studies have now aimed but failed to find rejection of scientific evidence on the left (e.g., Baumgaertner, Carlisle, & Justwan, 2018;Hamilton, Hartter, & Saito, 2015;Lewandowsky, Woike, & Oberauer, 2020). For example, Lewandowsky et al (2020) reported that vaccine-hesitancy and endorsement of alternative medicine-both anecdotally associated with a liberal worldview-were in fact more prevalent in right-wing libertarians and conservatives.…”
Section: Discussionmentioning
confidence: 99%
“…However, this presents future research with a conundrum, because a number of studies have now aimed but failed to find rejection of scientific evidence on the left (e.g., Baumgaertner, Carlisle, & Justwan, 2018;Hamilton, Hartter, & Saito, 2015;Lewandowsky, Woike, & Oberauer, 2020). For example, Lewandowsky et al (2020) reported that vaccine-hesitancy and endorsement of alternative medicine-both anecdotally associated with a liberal worldview-were in fact more prevalent in right-wing libertarians and conservatives. Based on additional evidence from a task that required reasoning about scientific evidence "dilemmas" that featured both worldview-consistent and inconsistent aspects, Lewandowsky et al concluded that partisans on both ends of the spectrum show biased processing of evidence, but that science denial was nevertheless a mainstay of the political right.…”
Section: Discussionmentioning
confidence: 99%